From «tribes» to the «production of locality». Representations of Sub-Saharan Africa - Τσεκένης Αιμίλιος (The Greek Review of Social Research, 2010)
The paper examines how scholars of sub-Saharan Africa have represented communities of sub-Saharan Africa. The first part examines the epistemological and political issues raised by the use of concepts such as «tribe» or «ethnic group». Attention is given to problems inherent to the concept itself as well as to the multiple ways by which African cultural and political institutions, and historical facts (such as the slave-trade, slavery, colonialism and their intertwining), contributed in the building of the concept of «tribe». The second part of the article sketches a brief definition of Kopytoff’s «African frontier», a paradigm which helped to overcome scientific and political objections posed by concepts such as «tribe». It goes on summarizing the critical assessment of the paradigm. The third and last part of the article shows in what sense concepts such as «locality» and «neighbourhood» forged in ethnographies of and in the present fit into the study of pre-colonial Cameroon Grassfields.